Conditioning Manager Alphas on Economic Information: Another Look at the Persistence of Performance - Christopherson, Jon A.; Ferson, Wayne E.; Glassman, Debra (Review of Financial Studies, 1998)
This article presents evidence on persistence in the relative investment performance of large, institutional equity managers. Similar to existing evidence for mutual funds, we find persistent performance concentrated in the managers with poor prior-period performance measures. A conditional approach, using time-varying measures of risk and abnormal performance, is better able to detect this persistence and to predict the future performance of the funds than are traditional methods.